The environment and human health: An agenda for research - V. S. Saravanan; Peter P. Mollinga (University of Bonn, Center for Development Research (ZEF), 2011)
The Working Paper Environment and Human Health gives a comprehensive review of the related literature in order to aid understanding of the (missing) link between the environment and health. Given the exhaustive literature on the subject the paper focuses on the water]related and land]related diseases namely in the fast growing and poor countries. By assessing the terrain of research on the subject, the paper aims to look beyond the causal linkage between environment and health and instead emphasis the underlying question about how environmental factors, along with man]made changes, influence human health. Specifically, the review examines the ability of the literature to define the incidence of environmentally]related diseases as well as their distribution across social and geographical scales, understands the role of diverse factors influencing these diseases and the adaptive capacity of societies in managing these illnesses or disorders. The paper draws on a wide range of sources from a variety of disciplines to unpack the linkage between the environment and health, and identifies issues, themes and questions raised by the literature. The review reveals limited understanding of the complex relationship between the environment and health. Although these researches provide grounds for a curative approach and in recent years have called for a preventive approach, they still retain a esimplistic high school modelf of examining the linear cause]effect relationship. This nevertheless fails to take on the growing risks posed by climate change and globalisation, as well as the dynamics of pathogens (and vectors) and of society affecting human health. These risks characterise complexity, uncertainty, conflicts and change. Given this characterisation of risks, the review calls for a modern approach to foresee and control the future consequences of human actions in order to live and adapt to the risks. This requires a comprehensive understanding of risk (from water pollutants) by identifying the pathways of risk assessment, understanding the impacts of pollutants and identifying a diverse set of strategies adopted by the individuals, organisations and agencies involved in bringing change to existing institutions and bio]physical resources.
Keywords: 330; Risk governance; globalization; fast growing economies; water governance; climate change